Successful Enzyme Colocalization Strategies in Yeast for Increased Synthesis of Non-native Products - Yocum, Hannah C.; Pham, Anhuy; Da Silva, Nancy A. (Frontiers in Bioengineering and Biotechnology, 2021)
Yeast cell factories, particularly Saccharomyces cerevisiae, have proven valuable for the synthesis of non-native compounds, ranging from commodity chemicals to complex natural products. One significant challenge has been ensuring sufficient carbon flux to the desired product. Traditionally, this has been addressed by strategies involving “pushing” and “pulling” the carbon flux toward the products by overexpression while “blocking” competing pathways via downregulation or gene deletion. Colocalization of enzymes is an alternate and complementary metabolic engineering strategy to control flux and increase pathway efficiency towards the synthesis of non-native products. Spatially controlling the pathway enzymes of interest, and thus positioning them in close proximity, increases the likelihood of reaction along that pathway. This mini-review focuses on the recent developments and applications of colocalization strategies, including enzyme scaffolding, construction of synthetic organelles, and organelle targeting, in both S. cerevisiae and non-conventional yeast hosts. Challenges with these techniques and future directions will also be discussed.